The Susceptibility to Persuasion Strategies Among Arab Muslims: The Role of Culture and Acculturation - Alnunu, Momin; Amin, Azzam; Abu-Rayya, Hisham M. (Frontiers in Psychology, 2021)
This study is set forth to explore whether the susceptibility to persuasion—as articulated by Cialdini’s persuasion strategies—could vary with culture and acculturation. We examined individuals from the Arabic culture and their susceptibility to persuasion, according to the following strategies: reciprocity, commitment, liking, scarcity, consensus, and authority. The study involved 1,315 Arab Muslims between 18 and 60 years old (Mean = 34.65, SD = 9.16). The respondents were recruited from among residents of the Arab region (n = 507), immigrant Arabs in non-Arabic Muslim countries (n = 361), immigrant Arabs in East Asian countries (n =85), and immigrant Arabs in Western countries (n = 362). Respondents completed an online Qualtrics survey. Controlling for socio-demographic variables (age, gender, income, education, and length of residence), our results indicated that susceptibility to the strategies differed significantly among Arab Muslims in the Arab region, with reciprocity being the highest and authority the lowest prevailing strategies. The same pattern of susceptibility emerged among immigrant Arab Muslims, regardless of their host country and the acculturation mode (integration, assimilation, separation, and marginalization) they endorse. These findings suggest that there is a consistent persuasion susceptibility pattern in the Arabic Muslim culture that does not seem to be modified by immigration and acculturation modes. Our findings are contrasted with the scarce research on cross-cultural differences in susceptibility to Cialdini’s persuasion strategies.